2012
DOI: 10.3892/mmr.2012.857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ascorbic acid and hydrogen peroxide on mouse neuroblastoma cells

Abstract: Ascorbic acid is one of the antioxidant compounds widely used against free radical stress. The present study was undertaken to examine whether ascorbic acid and hydrogen peroxide (H2O2), alone or in combination, could influence cell viability. The murine neuroblastoma cell line, N2a, was used to perform a dose response curve for ascorbic acid. It was observed that ascorbic acid alone at physiological concentrations (0.1–0.4 mM) did not cause any cell death. However, at pharmacological concentrations (1–6 mM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…2B). Lack of NAC toxicity in astroglial cells corroborated a similar viability result with ascorbic acid as previously reported (20). …”
Section: Resultssupporting
confidence: 91%
“…2B). Lack of NAC toxicity in astroglial cells corroborated a similar viability result with ascorbic acid as previously reported (20). …”
Section: Resultssupporting
confidence: 91%
“…Sub-optimal levels of peroxynitrite may also promote maximal mitochondrial superoxide formation through either CDM, uniquely dependent on the mitochondrial Ca 2+ accumulation triggered by RyR agonists [ 5 , 6 ], or RDM, taking place under conditions associated with suppression of electron transport, secondary to inhibition of complex III [ 4 , 6 ]. The enhancing effects mediated by AA in cells exposed to peroxynitrite and other oxidants were also described in other laboratories [ 30 , 31 , 32 ]. Although it is difficult to extrapolate the significance of experimental results obtained with cultured cells to draw conclusions relevant to human physio-pathology, reports in the literature describe deleterious effects mediated by acute supplementation of AA to individuals affected by β-thalassaemia major [ 33 ], as well as idiopathic haemochromatosis and dietary iron overload [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 58%
“…Intravenous administration of pharmacological concentrations of vitamin C also promotes cancer cell death in experimental animals [ 28 ] and in humans [ 29 ]. In addition, AA can be engaged in specific reactions leading to enhanced responses to specific reactive species [ 11 , 12 , 30 , 31 , 32 ]. As an example, we found that pre-exposure of U937 cells to AA enhances their susceptibility to the deleterious effects mediated by various hydroperoxides, in particular peroxynitrite [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 ) which could be an important contributory factor in resulting better cytotoxic effects during combination treatment against murine ascites Dalton's lymphoma and it is aided by decreased GSH levels in tumor cells as observed in the present study ( Table 2 ). Combination treatment of AA and H 2 O 2 has been reported to cause a significant decrease in GSH levels in the mouse neuroblastoma cells leading to effective death of cancer cells [57] . Increased cisplatin-induced apoptosis has been reported in ascorbate-supplemented cells by upregulation of MLH1 and p73 gene [58] .…”
Section: Discussionmentioning
confidence: 99%